2013
DOI: 10.1016/s1470-2045(13)70049-4
|View full text |Cite
|
Sign up to set email alerts
|

Cixutumumab and temsirolimus for patients with bone and soft-tissue sarcoma: a multicentre, open-label, phase 2 trial

Abstract: Summary Background Preclinical studies have shown synergistic antitumour activity by inhibition of insulin-like growth factor-1 receptor (IGF-1R) and mTOR. The expression of IGF-1R seems to be crucial for this effect. We investigated the safety and efficacy of the combination of the IGF-1R antibody cixutumumab and the mTOR inhibitor temsirolimus in patients with chemotherapy-refractory bone and soft-tissue sarcomas according to IGF-1R expression by immunohistochemistry. Methods We undertook a multicentre, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
126
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(135 citation statements)
references
References 19 publications
5
126
0
4
Order By: Relevance
“…Despite a wealth of preclinical information and two recent clinical trials demonstrating marked tumor regression in a subset of patients with EWS treated with combined antagonists of the IGF-1R/mTOR pathway, we noted a surprising lackluster cellular response to IGF-1R antagonists in conventional 2D monolayer culture (32,33). In seeking to elucidate biomarkers of response and mechanisms of de novo and acquired resistance, we hypothesized that this difference in preclinical and clinical response may result from inherent changes in the IGF-1R/mTOR signaling cascade when tumor cells are removed from their native microenvironment, which we sought to recapitulate using our 3D PCL scaffold while maintaining control over experimental parameters.…”
Section: Resultsmentioning
confidence: 81%
“…Despite a wealth of preclinical information and two recent clinical trials demonstrating marked tumor regression in a subset of patients with EWS treated with combined antagonists of the IGF-1R/mTOR pathway, we noted a surprising lackluster cellular response to IGF-1R antagonists in conventional 2D monolayer culture (32,33). In seeking to elucidate biomarkers of response and mechanisms of de novo and acquired resistance, we hypothesized that this difference in preclinical and clinical response may result from inherent changes in the IGF-1R/mTOR signaling cascade when tumor cells are removed from their native microenvironment, which we sought to recapitulate using our 3D PCL scaffold while maintaining control over experimental parameters.…”
Section: Resultsmentioning
confidence: 81%
“…29 These findings suggest that the activation mechanism of the Akt/mTOR pathway is multimodal and that we should seek a combination of drugs targeting not only mTOR but also the upstream receptors and the feedback loops. 31 At this point, we cannot conclude that any of the markers we studied are useful in making the decision whether targeting this pathway is the superior strategy for each patient. In the phase 2 study of ridaforolimus, 7 pAkt, pS6, and 4E-BP1 were not identified as good predictors of a clinically beneficial response.…”
Section: Discussionmentioning
confidence: 91%
“…Also, we need more effective agents for metastatic patients. There are ongoing clinical trials investigating monoclonal antibodies, small molecule inhibitors targeting the insulin like growth factor-1 receptor (Juergens et al, 2011;Tap et al, 2012;Schwartz et al, 2013). But most of them are phase I or II trials.…”
Section: Discussionmentioning
confidence: 99%